Science through storytelling or storytelling about science? Identifying cognitive task demands and expert strategies in cross-curricular STEM education - Barchas-Lichtenstein, Jena; Sherman, Melina; Voiklis, John; Clapman, Leah (Frontiers in Education, 2023)
While recent shifts away from sharply demarcated disciplines to cross-curricular K-12 education show great promise for enhancing students' interest and the relevance of subject matter, there remain many challenges to implementation as envisioned, not least among them teacher education. Most current teachers are socialized into disciplinary norms and identities through their pre-service education. To advance cross-curricular teaching, then, teachers need support, including more attention to the instructional design of teacher-facing materials. Without attention to teachers as learners, teachers will continue to implement promising educational innovations only through the lens of their discipline. Using a cognitive interview methodology, we asked how teachers with professional formation in different disciplines would approach a project that purported to connect those disciplines. On the one hand, we found that lesson planning and implementation is a broadly similar task for various types of teachers. On the other hand, we also found that, for the most part, both science and journalism educators focused more heavily on the aspects of a science journalism project that fit within their own discipline. Yet all teachers we interviewed were interested in the possibilities a cross-curricular project opens, which suggests the need for further research on implementation and uptake.